Self‐care among older people living with chronic conditions. (24th March 2018) - LeBlanc, Raeann G.; Jacelon, Cynthia S.
Abstract : Purpose: The aim of this study was to clarify the concept of self‐care among older people living with chronic health conditions. This concept clarification will assist nurses in addressing self‐care among older people through research, policy and practice in offering an expanded conceptual model. Background: Several policy influences over the past decade directly relate to the increased importance and economic necessity to require self‐directed care for older people living with chronic health conditions to maintain their care at home in the community. Method: A selective review of literature on the concept of self‐care included 31 sources. The Norris Concept Clarification method (1982) was used for clarification. The phenomenon is described historically according to its antecedents, attributes and consequences. Results: A proposed definition is provided based on the clarification of this concept. A conceptual model is presented through an ecological framework. Self‐care among older people living with chronic conditions is multidimensional and has multilevel influences (individual, community, system levels) and is mediated by the contexts and processes of ageing. Self‐care originates along one's life course and is learned. Self‐care responses are based on care needs when living with chronic health conditions. Conclusion: Self‐care is an individual capacity, disposition and activity older people manifest in living with multiple chronic conditions. These features (capacity, disposition, action) influence one another and are hierarchical and continuous. Research, practice and policies that promote self‐care among older people can focus on these features to improve health outcomes and promote new models of care consistent with personal development and chronic care needs in older age. Implications for practice: This concept clarification can offer a model to support self‐care among older people living with chronic conditions.